Diversidade biológica: regulamentação jurídica do patrimônio genético - Cordeiro, Idelcleide Rodrigues Lima (2015)
Concern for the defense of biodiversity has been growing in recent years due to the progress of life sciences, especially in the areas of genetic engineering, molecular biology and modern biotechnology. This dissertation, whose theme biological diversity, the legal regulation of genetic resources and associated traditional knowledge, addresses the importance of preserving biodiversity, aiming to demonstrate the need to create efficient legal instruments for their protection. It adopted the method of deductive approach using the indirect documentation and literature through books, journals and virtual vehicles related to the topic. Initially, the study presents the key issues of biodiversity, discussing the evolution of this concept, as well as the genetic heritage of notions and associated traditional knowledge. It demonstrates the potential of biodiversity in Megadiverse Countries. Addresses the relationship of biodiversity with biotechnology and biopiracy, highlighting the cases of global impact and the factors that encourage biopiracy. It discusses the importance of traditional communities as environmental preservation factor. Then deals with the legal protection of biodiversity, analyzing the UN's role in environmental protection, environmental principles and national legal instruments of access to genetic resources and associated traditional knowledge. The research highlights the prospects for the development of the Brazilian Amazon from the exploitation of their genetic heritage, demonstrating the need to seek a balance between economic use of components of biodiversity, so pace and such that do not lead to depletion of natural resources while maintaining the potential to meet the aspirations of present and future generations, highlighting the urgent need to reconcile the conservation of the immense potential for natural resources in the Amazon with the consolidation of a sustainable development policy and effective legislation. Finally, defines the regulatory power under administrative law, has a regulatory proposal Protection Act of genetic resources and associated traditional knowledge of Acre, in order to ensure faithful implementation of Acre law and contribute to reducing the undue access Natural products. Thus, it appears that Amazon should be protected for its importance in the national context, protecting the Brazilian State of improper of their genetic heritage and associated traditional knowledge appropriation.